Designing a Sulfur Vacancy Redox Disruptor for Photothermoelectric and Cascade-Catalytic-Driven Cuproptosis–Ferroptosis–Apoptosis Therapy - Xu, Mengshu; Liu, Jingwei; Feng, Lili; Hu, Jiahe; Guo, Wei; Lin, Huiming; Liu, Bin; Zhu, Yanlin; Li, Shuyao; Berdimurodov, Elyor; Sharipov, Avez; Yang, Piaoping (Nano-Micro Letters, 2025)
The therapeutic efficacy of cuproptosis, ferroptosis, and apoptosis is hindered by inadequate intracellular copper and iron levels, hypoxia, and elevated glutathione (GSH) expression in tumor cells. Thermoelectric technology is an emerging frontier in medical therapy that aims to achieve efficient thermal and electrical transport characteristics within a narrow thermal range for biological systems. Here, we systematically constructed biodegradable Cu2MnS3-x-PEG/glucose oxidase (MCPG) with sulfur vacancies (SV) using photothermoelectric catalysis (PTEC), photothermal-enhanced enzyme catalysis, and starvation therapy. This triggers GSH consumption and disrupts intracellular redox homeostasis, leading to immunogenic cell death. Under 1064 nm laser irradiation, MCPG enriched with SV, owing to doping, generates a local temperature gradient that activates PTEC and produces toxic reactive oxygen species (ROS). Hydroxyl radicals and oxygen are generated through peroxide and catalase-like processes. Increased oxygen levels alleviate tumor hypoxia, whereas hydrogen peroxide production from glycometabolism provides sufficient ROS for a cascade catalytic reaction, establishing a self-reinforcing positive mechanism. Density functional theory calculations demonstrated that vacancy defects effectively enhanced enzyme catalytic activity. Multimodal imaging-guided synergistic therapy not only damages tumor cells, but also elicits an antitumor immune response to inhibit tumor metastasis. This study offers novel insights into the cuproptosis/ferroptosis/apoptosis pathways of Cu-based PTEC nanozymes. Highlights: 1 The glycometabolism and enzyme activity of Cu2MnS3-x-PEG/glucose oxidase (MCPG) achieve a cascade catalytic reaction, continuously replenishing the deficient H2O2 and O2 and inducing adequate reactive oxygen species supply. 2 Density functional theory calculations indicate that Mn doping facilitates the structural reconstruction and evolution of sulfur vacancies (SV) sites, leading to a remarkable increase in the catalytic activity of Cu2MnS3-x. 3 Under 1064 nm laser irradiation, MCPG with abundant SV drives charge carrier diffusion from hotter to cooler regions, thus creating a potential difference and activating the photothermoelectric catalysis.